Cascade of care for hypertension among apparently healthy and unhealthy individuals of 25-64 years in the Czech Republic - Berka, Barbora; Lustigová, Michala; Urbanová, Jana; Krollová, Pavlína; Hloch, Ondřej; Romanová, Alexandra; Michalec, Juraj; Taniwall, Arian; Žejglicová, Kristýna; Malinovská, Jana; Jenšovský, Michael; Vejtasová, Veronika; et al. (PloS one, 2024)
BACKGROUND: Despite accessible diagnostics and treatment of hypertension, a high proportion of patients worldwide remain unaware of their diagnosis, and even more remain untreated. Several studies suggest that absence of comorbidities is a predictive factor for unawareness and consequently non-treatment of hypertension. There are only a few studies that have assessed the hypertension prevalence and management among apparently healthy individuals. OBJECTIVE: The aim of the study was to assess and compare hypertension prevalence, awareness, treatment and control among apparently healthy individuals, patients with internal diseases, and patients with non-internal diseases. METHODS: Data from standardised blood pressure measurements conducted during the Czech European Health Examination Survey 2014 and information on health status and health care use collected during the Czech European Health Interview Survey 2014 were analyzed. We focused on participants aged 25-64. Data were weighted on sex and age to ensure an appropriate sex and age structure of the population. The χ2-test and binary logistic regression analyses were used to compare distribution of cascade of care for hypertension between the health-status groups of respondents. RESULTS: The final eligible sample consisted of 1121 participants. The prevalence of hypertension was 32.8% in the healthy group, 29.8% in the non-internal disease group and 52.4% in the internal disease group, (p < 0.001). Awareness was 54.1%, 59.1% and 85.2% respectively, (p < 0.001). Treatment was 44.2%, 52.6% and 86.4%, respectively, (p < 0.001). Among apparently healthy respondents 62.6% had their blood pressure measured by a medical professional in the last year, compared to 71.1% in the non-internal disease group and 91.7% in the internal disease group, (p < 0.001). Differences in hypertension control were not statistically significant. CONCLUSIONS: Generally, our data show a discordance in hypertension management within the Czech population. Apparently healthy individuals are the least aware of their diagnosis and the highest proportion of them remain untreated.
Keywords: mužské pohlaví; Male; Czech Republic; Humans; Female; Health Knowledge, Attitudes, Practice; lidé; Middle Aged; ženské pohlaví; lidé středního věku; zdravotnické přehledy; Česká republika; Prevalence; krevní tlak; zdraví - znalosti, postoje, praxe; Blood Pressure; hypertenze; dospělí; Adult; Hypertension; prevalence; Health Surveys